1940
DOI: 10.6028/jres.024.013
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, in roentgens, of the gamma radiation from radium by the free-air ionization chamber

Abstract: The free-air ionization chamber is the accepted standard for calibrating X-ray dosage measuring instruments. With the advent of supervoltage X-r ays, the need for proved standards for this range has arisen.The present paper describes an investigation of the applicability of the free-air pressure ionization chamber for measuring radiation at the high-frequency end of the X-ray spectrum, that of the gamma radiation from radium.Measurements were made with a narrow collimated beam of gamma rays at pressures up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1944
1944
1987
1987

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The same difficulty was encountered in the measurement of absorbed X-ray energy, when it was found that the parallel plate chamber which effectively measured X-ray ionization in an extended gaseous medium and was satisfactory for voltages up to 200 kV., became too clumsy an instrument when made on a scale adequate for the measurement of high-voltage X-rays or y-rays. The most convenient solution of this difficulty has proved to be by the use of very small ionization chambers which, if constructed of suitable material, have been shown experimentally to yield the same value for the ionization per unit volume of the enclosed gas as would be observed with a parallel plate chamber of appropriate dimensions (52,80). The underlying principle is as follows.…”
Section: The Principles Of the Ionization Methods Of Measuring Neutronmentioning
confidence: 99%
“…The same difficulty was encountered in the measurement of absorbed X-ray energy, when it was found that the parallel plate chamber which effectively measured X-ray ionization in an extended gaseous medium and was satisfactory for voltages up to 200 kV., became too clumsy an instrument when made on a scale adequate for the measurement of high-voltage X-rays or y-rays. The most convenient solution of this difficulty has proved to be by the use of very small ionization chambers which, if constructed of suitable material, have been shown experimentally to yield the same value for the ionization per unit volume of the enclosed gas as would be observed with a parallel plate chamber of appropriate dimensions (52,80). The underlying principle is as follows.…”
Section: The Principles Of the Ionization Methods Of Measuring Neutronmentioning
confidence: 99%